Effectiveness Of Decoction Of Ciplukan Plants (Physalis Angulata L) As Anti-Hypercholesterolemia In Rundeng Village, Johan Pahlawan District, West Aceh Regency - Syachyan, Nur; Nasution, Nurromsyah; Febrianti, Yurica; Aulia, Yulfa; Aida, Nurul Siti (Institute Of Computer Science (IOCS), 2024)
Hypercholesterolemia has become a health problem in developing countries such as Europe, America and Southeast Asia. Hypercholesterolemia can be reduced with non-pharmacological therapy, one of which is by consuming a decoction of the Ciplukan Plant (Physalis Angulata L). The Ciplukan plant (Physalis angulata L) contains many secondary metabolite compounds, namely flavonoids and phenolics such as physalin, physagulin, beta-carotene, myricetin, oleanolic acid and quercetin which have very good effectiveness in reducing plasma lipid levels in sufferers of hypercholesterolemia. The aim of this research was to determine the effectiveness of a decoction of the Ciplukan plant (Physalis Angulata L) as an antihypercholesterolemia in Rundeng Village, Johan Pahlawan District, West Aceh Regency. The design used was